The electronic structures of solids - Coles, B. R. (The estructures and properties of solids, 1976)
Electronic structure of atoms - Bonding between atoms - Electrons in metals: the free-electron gas - Electrons in metals: interaction with the crystal lattice - Metals, insulators and semiconductors - Special topics.